Efektivitas Multimedia dalam Pembelajaran Interaktif Berbasis Kurikulum Merdeka di Kelas IX SMPN 25 Tangerang - Musyaffa’ Rafif Naufal; Hindun Hindun (Universitas Maritim AMNI Semarang, 2024)
Students who are not active in class may be caused by factors that do not directly involve them in the learning process. Therefore, teachers are expected to design appropriate learning facilities to make students more interested and understand the material conveyed by the teacher. The lack of mastery of technology in the classroom learning activities results in low active participation of students, as the learning media is less engaging and does not provide concrete experiences. This study aims to analyze and describe the effectiveness of multimedia in interactive learning based on the independent curriculum. Data collection was carried out through the distribution of questionnaires in the form of Google Forms to 35 students of Grade IX at SMPN 25 Tangerang. This study used a qualitative descriptive approach to elaborate and describe the data that has been found. The results of the data analysis and this study indicate that the effectiveness of using multimedia in interactive learning based on the independent curriculum in Grade IX at SMPN 25 Tangerang is proven to be very effective in supporting an interesting and interactive classroom environment.